DEGRADASI ASAM FITAT SORGUM (Sorghum bicolor L. Moench) MELALUI FERMENTASI BAKTERI ASAM LAKTAT - , Rikka Welhelmina Sir ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fermentation with lactic acid bacteria (LAB) owning phytase activity could reduce levels of phytate in foodstuffs. This study was aimed to screen of LAB that have a high phytase activity, and how its ability to reduce levels of phytic acid during fermentation, as well as to determine the digestibility of starch and protein changes as a result of the fermentation. The results of 48 test isolates showed that 20 isolates of LAB which has phytase activity was indicated by the presence of a clear zone on MRS-MOPS medium modifications. Isolates that had the highest activity was BAL S 5422 The acticity was 0.735 U/ml and 1,103 U/ml in incubation temperature of 300C and 370C, respectively. Sorghum fermentation using inoculum BAL S 5422 was not different from the spontaneous fermentation. Both are able to reduce the phytic acid 45.68% and also increase starch digestibility from 30.02% to 39.00% and increase protein digestibility from 59.56% to 79.09%. The addition of inoculum BAL S 5422 does not cause a noticeable difference in the increase in the digestibility of starch and protein